Program Effectiveness “Ally Micuy” in improving the nutritional status of children under 36 months Chacas district, Ancash Region, Peru - Brañes Hermitaño, Daisy Danitza (2019)
Objective: To determine the effectiveness of the “Ally Micuy” in improving the nutritional status of childrenunder 36 months Chacas District, Ancash Region. Methods: The study design is pre experimental, populationand sample were 122 children. For data collection sheet was used monitoring the children, which recordedanthropometric data (height / age), hemoglobin (g / dl according to high level) and knowledge of mothers. Inimplementing the “Ally Micuy” was searched comprehensively improve the quality of life of the participatingmothers through various individual and group activities. Results: Before 5% unknown Programme concernedabout food issues, this increased to 90% after the intervention, on the other hand the difference in hemoglobinvalues according to statistical analysis comparing means for related samples was in response before the programan average of 10.4 g / dl and postoperatively an average of 11.0 g / dl with a difference of 0,000 Sig. Regardingchronic malnutrition most significant age groups were 6-11 months with a difference of Sig = 0.008, 12-17months with a difference of Next 18-23 Months = 0.012 and a difference of Sig =. 000. Conclusions: TheProgram “Ally Micuy” is effective in improving the nutritional status because increased knowledge of mothers,the value of Hb and decreased the prevalence of chronic malnutrition.